Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Kontekstual pada Pembelajaran IPA Kelas IV SD - Mila Sartika; Elya Rosalina; Aswarliansyah Aswarliansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to develop Contextual-based worksheet designs. Testing the validity and practicality of contextual-based worksheets on various styles for elementary school students. This type of research is Research and Development with the 4D development model. The subjects of this study were 6 students and fourth grade students at SD Negeri 3 Muara Beliti. Data collection techniques using interviews, observation, and questionnaires. Based on the results of LKPD validation, the results of the assessment of linguists with a score of 0.87, material experts with a score of 0.80 and media experts with a score of 0.87. Meanwhile, from the analysis of the assessment of the practicality of the teacher's sheet, a score of 90.6% was obtained and the practicality of the students obtained a score of 83.3%. Based on the results of the study it can be concluded that contextually based LKPD is proven to be valid, and practical in learning material of various styles for elementary school students. Keywords: Development, LKPD, Contextual, Elementary School